Produtos meliponícolas de abelha jandaíra (melipona subnitida) do SEMIÁRIDO potiguar - Luz, Kewen Santiago da Silva (Universidade Federal Rural do Semi-Árido, 2021)
The objective of this study was to identify the technological evolution of the stingless bees’ products and to characterize the fresh and matured honey, the geopropolis and the saburá of Melipona subnitida. Four patent databases were consulted, Patentscope, Espacenet, LATIPAT, INPI. Thirty honey samples, ten geopropolis samples and six saburá samples were also collected in different cities in the semi-arid region of Rio Grande do Norte state, Brazil. The physical-chemical, microbiological, and sensory characteristics of the geopropolis samples, the hydroethanolic extracts of geopropolis, the fresh honey samples and the saburá samples were evaluated. The honey characteristics were also evaluated during the 120-day maturation process. 58 filed patents were found related to stingless bee products in the world. Brazil has been highlighted for presenting 41,4% of all filed patents analyzed. The analysis of the IPC classification codes showed that 29,3% of patent documents were registered in subclass A61K 35/644 of medicinal preparations containing beeswax, propolis, royal jelly or honey. The mineral content in the geopropolis samples in natura varied from 37,5 to 82,0 g/100 g. It was possible to observe in the extracts pH variations between 4,15 to 5,9, density between 0,796 to 0,859 g/cm3, dry residue content between 1,0 to 17,9 g/100 ml, content of total phenolic compounds 3,2 to 41,7 mg EAQ/g, flavonoids 1,2 to 49,0 mg EQ/g and EC50 0.16 to 4.16 μg/ml. Regarding the antimicrobial activity of the extracts, it was possible to identify higher values of inhibition against gram-positive microorganisms than gram-negative strains, however most of the extracts were able to inhibit microbial growth. Both the fresh geopropolis and the geopropolis hydroethanolic extracts showed a variety of sensory characteristics. The only microorganisms detected in fresh honey samples were molds and yeasts with microbial count values ranging between <1,18 to 4,85 Log10 CFU/g. In the fresh samples, average values of humidity were found: 26,5 g/100 g; pH 3,5; free acidity 36,14 mEq/kg; hydroxymethylfurfural 6,15 mg / kg; reducing sugars 67,58 g/100 g; apparent sucrose 2,89 g/100 g; water insoluble solids 0,1 g/100 g, ash 0,27 g/100 g and 44% of the analyzed samples showed water white color (0 to 8 mm Pfund). At the initial time of maturation, honey presented molds and yeasts, 3,6 ± 0,4 Log10 CFU/g, total mesophilic bacteria 4,1 ± 0,2 Log10 CFU/g and lactic acid bacteria 4,3 ± 0,1 Log10 CFU/g, but after the first month of maturation, the presence of these microorganisms in the samples was almost zero (<1,2 and <1,5 Log10 CFU / g). It was observed that the pH of honey is an important measure to identify the changes that occur during the maturation. During the 120 days of the process, the pH gradually became more acidic, while the acidity content increased (r = -0,945; p <0.001), the reducing sugar content decreased (r = 0,962; p <0,001) and honey it became denser (r = -0,861; p <0,001). After 120 days of the maturation process, the honey showed an acidic aroma, bittersweet flavor, the color and the liquid consistency were unchanged. There was no detection of microorganisms in the analyzed saburá samples, indicating that the biochemical and microbial processes managed by the stingless bees were efficient in inhibiting the product deterioration. As for the physical-chemical parameters, the samples of saburá showed average moisture content of 27,2 g/100 g; protein 31,1 g/100 g; total sugars 55,2 g/100 g; pH 3,5 and acidity 1023,7 mEq/kg. The jandaira products have great market potential due to their different characteristics and biological properties
Keywords: Meliponini; Propriedade Intelectual; Bioativos naturais; Processos fermentativos; Meliponini; Intellectual property; Bioactive potential; Fermentation processes; CIENCIAS AGRARIAS::MEDICINA VETERINARIA